When do environmental disclosure and environmental performance improve financial performance? The moderating effect of environmental costs - Deavita Kholisna; Ida Nur Aeni (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study aims to examine the effects of environmental disclosure and environmental performance on financial performance, with environmental costs serving as a moderating variable. A quantitative approach was employed using panel data regression on basic materials sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period, resulting in a total of 253 observations selected through purposive sampling. Financial performance was measured using Earnings per Share (EPS), environmental disclosure was assessed based on the Global Reporting Initiative (GRI) standards, and environmental performance was evaluated using the PROPER rating. The findings indicate that environmental disclosure has a significant effect on financial performance, whereas environmental performance does not. Environmental costs were found to moderate the relationship between environmental disclosure and financial performance but were unable to moderate the relationship between environmental performance and financial performance. These results suggest that transparent environmental information, when supported by a strong commitment to environmental expenditure, can enhance a company's financial performance.